Uslūb al-Ḥakīm wa Sūrat al-Baqarah - Fairuz Subakir Ahmad (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Uslūb al-Ḥakīm is one of the rhetorical devices (al-muḥassināt al-badīʿiyyah) in Arabic rhetoric. Scholars differ on whether Uslūb al-Ḥakīm and al-qawl bi al-mūjab represent the same rhetorical phenomenon or two distinct forms. As a rhetorical embellishment, Uslūb al-Ḥakīm appears in both Arabic poetry and prose, enriching discourse through its aesthetic and semantic dimensions. It is also found in the Qur’anic text, including Sūrat al-Baqarah, the longest chapter of the Qur’an. Understanding this rhetorical style requires readers to possess a comprehensive knowledge of its meanings and functions. The occurrences of Uslūb al-Ḥakīm in Sūrat al-Baqarah can be classified into two principal forms. The first occurs when a speaker uses a word or expression, and the respondent adopts that same word but redirects its meaning, constructing a new statement based on the altered interpretation or offering a subtle comment derived from the reversed meaning. The second occurs when a question is answered with a response that appears unrelated to the original inquiry, intentionally redirecting the discussion toward a more important, beneficial, or appropriate matter. This rhetorical strategy highlights the wisdom and eloquence of Qur’anic discourse.